Monitoring Conformation and Protonation States of Glutathione by Raman Optical Activity and Molecular Dynamics - Das, Moumita; Gangopadhyay, Debraj; Hudecová, Jana; Kessler, Jiří; Kapitán, Josef; Bouř, Petr (ChemPlusChem, 2023)
Glutathione (GSH) is a common antioxidant and its biological activity depends on the conformation and protonation state. We used molecular dynamics, Raman and Raman optical activity (ROA) spectroscopies to investigate GSH structural changes in a broad pH range. Factor analysis of the spectra provided protonation constants (2.05, 3.45, 8.62, 9.41) in good agreement with previously published values. Following the analysis, spectra of differently protonated forms were obtained by extrapolation. The complete deprotonation of the thiol group above pH 11 was clearly visible in the spectra; however, many spectral features did not change much with pH. Experimental spectra at various pH values were decomposed into the simulated ones, which allowed us to study the conformer populations and quality of molecular dynamics (MD). According to this combined ROA/MD analysis conformation of the GSH backbone is affected by the pH changes only in a limited way. The combination of ROA with the computations thus has the potential to improve the MD force field and obtain more accurate populations of the conformer species. The methodology can be used for any molecule, but for a more detailed insight better computational techniques are needed in the future.
Keywords: spectra modeling; Molecular Dynamics Simulation; Raman optical activity; glutathione; molekulární konformace; Optical Rotation; molecular dynamics; optická otáčivost; simulace molekulární dynamiky; glutathion; density functional theory; Glutathione; Spectrum Analysis, Raman; Molecular Conformation; Ramanova spektroskopie